Panteizm i ateizm Johanna Wolfganga Goethego. Istotny wkład w rozwój europejskiej kultury filozoficznej od teizmu do ateizmu - Szocik, Konrad (Slavia Occidentalis, 2011)
The text is an attempt to define religious and theological views of Goethe. The author’s reflections focus on Goethe’s poem “Prometheus” in which the poet polemises with the Christian idea of God. The poem outlines the anthropological genesis of religion and the concept of God. The inspiration for Goethe’s philosophical considerations was nature seen as God’s realm, the rejection of the belief that God is a transcendental being, and, consequently, the rejection of the anthropological concept deifying man. Goethe’s thought reflects a modern, European perspective concentrated on the world and man, abandoning all ideological restraints.